2014
DOI: 10.1371/journal.ppat.1003889
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Host-Derived Sphingosine by Pseudomonas aeruginosa Is Important for Survival in the Murine Lung

Abstract: Pseudomonas aeruginosa is a common environmental bacterium that is also a significant opportunistic pathogen, particularly of the human lung. We must understand how P. aeruginosa responds to the lung environment in order to identify the regulatory changes that bacteria use to establish and maintain infections. The P. aeruginosa response to pulmonary surfactant was used as a model to identify transcripts likely induced during lung infection. The most highly induced transcript in pulmonary surfactant, PA5325 (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 73 publications
4
61
0
Order By: Relevance
“…In this context, fermentative anaerobes aspirated from the oral cavity that become established in the lower airways may play a central role in the progression of CF lung disease. Expectorated sputum and many of its specific constituents-lipids [15,17], amino acids [16], and modified sugars [40], for example-are known to support bacterial growth in vitro and have been studied in detail. Yet, how the majority of these compounds are made available within the CF airways has not been defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, fermentative anaerobes aspirated from the oral cavity that become established in the lower airways may play a central role in the progression of CF lung disease. Expectorated sputum and many of its specific constituents-lipids [15,17], amino acids [16], and modified sugars [40], for example-are known to support bacterial growth in vitro and have been studied in detail. Yet, how the majority of these compounds are made available within the CF airways has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory tract contains a number of host compounds that can be used by microbes as nutrient sources, including immunoglobulins, cytokines, defensins and lactoferrin [8,9], yet these are unlikely to be present at concentrations to support the dense microbiota of the CF airways [10][11][12][13]. Additionally, studies of CF sputum from adult patients have shown an abundance of small molecules that can support the growth of pathogens in vitro, including sugars, fatty acids, phospholipids, and amino acids [14][15][16][17]. However, the mechanism by which these compounds reach high abundance in airway mucus remains poorly defined.…”
Section: −10mentioning
confidence: 99%
“…Thus, ceramide acts by re-organizing molecules in cells and can control many receptor-mediated and non-receptor-mediated cellular activation processes by changing the biophysics of the membrane. In accordance, ceramide-enriched membrane platforms have been shown to be formed in cells after the application of a variety of stimuli, including CD95 , CD40 (Grassmé et al, 2002), DR5 (Dumitru and Gulbins, 2006), FcγRII (Abdel Shakor et al, 2004), and the PAF-receptor (Göggel et al, 2004); infection with P. aeruginosa (Grassmé et al, 2003a), Neisseriae gonorrhoeae (Grassmé et al, 1997), Neisseria meningitides (Simonis et al, 2014), rhinovirus (Grassmé et al, 2005), or measles virus (Gassert et al, 2009;Avota et al, 2011); or stress stimuli such as UV-light (Charruyer et al, 2005), gamma-irradiation (Rotolo et al, 2005), or treatment with cisplatin (Lacour et al, 2004) or Cu 2+ (Lang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At least P. aeruginosa PAO-1 expresses sphingosine response elements, i.e. sphA, which are specifically induced by sphingosine via a sphingosine-specific transcription factor (PA5324), a member of the AraC-family transcription factor, named SphR [39]. Deletion of the SphR transcription factor resulted in reduced bacterial survival during mouse lung infection and increased sensitivity of the pathogen to the antimicrobial effects of sphingosine.…”
Section: Discussionmentioning
confidence: 99%